1995
DOI: 10.1109/10.464380
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of motion artifacts using a two-frequency impedance plethysmograph and adaptive filtering

Abstract: We measured transthoracic impedance in nine presumed healthy adult subjects with a two-frequency plethysmograph at 57 kHz and 185 kHz. The measurement protocol included periods of normal breathing without motion and periods of motion without breathing. We analyzed the cross-correlation and the ratio between the signals at both frequencies for all the different maneuvers. The correlation coefficient was between 0.97 and 1 for breathing, the minimal cross-correlation (0.81) was for simulated obstructive apnea. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The steady and pulsatile components of the PPG signal. dardization of cuff application and automation of the pressure measurements [39]. This showed that systolic ankle pressure measurements could become less operator dependent [40].…”
Section: Ppg and Ankle Brachial Pressure Indexmentioning
confidence: 98%
“…The steady and pulsatile components of the PPG signal. dardization of cuff application and automation of the pressure measurements [39]. This showed that systolic ankle pressure measurements could become less operator dependent [40].…”
Section: Ppg and Ankle Brachial Pressure Indexmentioning
confidence: 98%
“…However, motion is another main source of blood volume variation. Motion can create drastic variations in the measured IP signal [18]- [22], resulting in artifacts whose amplitudes are much larger than the amplitude of the respiratory component in many cases [23]. As a result, it is necessary to use filtering methods to eliminate MA's before the signal can be used to monitor respiration.…”
Section: Impedance Plethysmography and Respiratory Ratementioning
confidence: 99%
“…The Pearson correlation coefficient between S p,n g −y and S q,n g −y is defined as r pq = s pq √ s pp s qq (23) where s pq is the covariance between S p,n g −y and S q,n g −y and s pp is the variance of S p,n g −y . Thus,…”
Section: Gradientsmentioning
confidence: 99%
“…For the realization of the respiration sensor we decided against RIP-based sensors as they are still relatively expensive and difficult to handle [1]. Furthermore, we excluded impedance plethysmography because of its sensitivity to body movements [11] which would result in motion related artifacts during physical exercise. Our initial choice was a piezoelectric film, but during preliminary tests we observed a high edge steepness in relation to the applied pressure during in-and exhalation.…”
Section: Construction Of Respiration Sensormentioning
confidence: 99%